2003
DOI: 10.3354/meps246127
|View full text |Cite
|
Sign up to set email alerts
|

Are there activated chemical defenses in sponges of the genus Aplysina from the Caribbean?

Abstract: The Mediterranean sponge Aplysina aerophoba has been proposed to rely on damageinduced activation of chemical defenses against pathogens and fish predators. High molecular weight brominated tyrosine derivatives have been suggested to undergo rapid, enzyme-mediated transformations into the metabolites aeroplysinin-1 and dibromocyclohexadienone following tissue damage, a process also called 'biotransformation'. These putative end-products were found to exhibit greater defensive activity compared to their precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…Thoms et al (71) also found significant differences in the concentrations of secondary metabolites between specimens of A. aerophoba collected in Croatia and France, supporting the idea that chemical variation seems to be common within species of the genus Aplysina (55). Similarly, several bacteria differed between A. aerophoba, Geodia barretti, and Cymbastela concentrica (35,41,66).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Thoms et al (71) also found significant differences in the concentrations of secondary metabolites between specimens of A. aerophoba collected in Croatia and France, supporting the idea that chemical variation seems to be common within species of the genus Aplysina (55). Similarly, several bacteria differed between A. aerophoba, Geodia barretti, and Cymbastela concentrica (35,41,66).…”
Section: Discussionmentioning
confidence: 60%
“…Similarly, the alkaloid content remained unchanged after cultivation of Aplysina specimens in starvation conditions and antibiotics exposure in aquaria (35). Nevertheless, other studies with emphasis on natural products quantification show considerable variability in the concentration of secondary metabolites within Aplysina species (55) and between specimens of the same Aplysina species (62). The relative composition of the main brominated compounds under ex situ and in situ cultivation of A. aerophoba remained stable, although the total alkaloid content increased twice as much ex situ than in situ (43).…”
Section: Discussionmentioning
confidence: 92%
“…4). For tissue samples of A. cauliformis from the Florida Keys and Bahamas Islands, fistularin 3 occurred at 2.4 mg/mL of sponge volume (SD = 1.1, n = 59) and, unlike other Aplysina species, had very low levels of other related metabolites in its tissues (24,25). Other Aplysina species, including Aplysina fulva, which ranked sixth most abundant across all sites, also had fistularin 3 as a dominant chemical defense (24).…”
Section: Discussionmentioning
confidence: 99%
“…Of the sponge species tested for the present study, Callyspongia armigera, Iotrochota birotulata and Niphates erecta lacked chemical defenses (Pawlik et al 1995), while Amphimedon compressa produces a pyridinium alkaloid that is highly deterrent to predators (Albrizio et al 1995), Aplysina spp. contain unpalatable brominated tyrosine derivatives (Puyana et al 2003, Nuñez et al 2008 and Ptilocaulis walpersi contains deterrent bromopyrroles and oroidin-class metabolites similar to members of the genus Agelas (Wright et al 1991, Assmann et al 2000. The biosynthetic pathways for sponge secondary metabolites are poorly understood, but the process is likely to be costly, as may also be the storage of metabolites and the prevention of autotoxicity (Van Alstyne et al 2001).…”
Section: Growth and Chemical Defensementioning
confidence: 99%
“…Some of the secondary metabolites responsible for deterrent activity in defended sponges have been isolated and identified (e.g. Albrizio et al 1995, Puyana et al 2003, Nuñez et al 2008. Assuming these complex compounds require metabolic energy to synthesize, store and deploy, a trade-off between chemical defenses and growth in sponges would be expected.…”
Section: Introductionmentioning
confidence: 99%